Implementasi Service Learning dalam Edukasi Kesehatan, Keselamatan, dan Gizi Anak Usia Dini di Pusat Tumbuh Kembang Anak UIN Alauddin Makassar - Jamilah; Damayanti, Eka; Sofyan; Majid, Ahmad Farham (Faculty of Tarbiyah and Teacher Training, 2026)
Ensuring health, safety, and adequate nutrition is essential for optimal early childhood development. This community service program aimed to strengthen children’s and caregivers’ understanding of healthy behavior, everyday safety, and balanced nutrition through a service-learning approach at the UIN Alauddin Makassar Child Growth and Development Center. Conducted from May to June 2025, the program involved 20 undergraduate students, 2 caregivers, and 15 children. It comprised three stages: pre-implementation, implementation, and post-implementation. Educational activities included posters, storytelling, guided meal practice, personal-hygiene checks, and height and weight measurement. Outcomes were evaluated qualitatively through observation of participants’ responses, children’s ability to retell key messages, and reflection involving students, lecturers, and caregivers. The children participated actively and were able to restate the main messages in age-appropriate language. Caregivers also gained practical guidance for reinforcing healthy, safe, and nutritionally balanced routines. The program demonstrates that service learning can connect student learning with community needs; however, changes in knowledge and behavior were not measured using standardized instruments.